2018
DOI: 10.1002/cphc.201701254
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Absorption and Electronic Circular Dichroism Spectra of (R)‐(+)‐1‐Phenylethanol. Confident Interpretation Based on the Synergy between Experiments and Computations

Abstract: Using density functional theory and its time-dependent extension for excited states, the S →S high-resolution vibronic absorption and electronic circular dichroism spectra of (R)-(+)-1-phenylethanol are computed and compared to experimental spectra measured in jet-cooled conditions in the region within 1000 cm of the 0-0 transition. The agreement between theory and computation is satisfactory and allows a confident assignment of several experimental bands in terms of fundamentals of different modes. Cases are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…In the course of the latter work, theoretical calculations predicted the presence of a vibronic band which was originally not resolved in the experiments. Based on those predictions, the experiments were recorded with a higher resolution and, interestingly, the predicted band could be resolved, and its anisotropy factor was shown to be correctly predicted, as demonstrated in Figure …”
Section: Spectroscopic Methods To Analyze Products Of Model Heterogenmentioning
confidence: 88%
See 4 more Smart Citations
“…In the course of the latter work, theoretical calculations predicted the presence of a vibronic band which was originally not resolved in the experiments. Based on those predictions, the experiments were recorded with a higher resolution and, interestingly, the predicted band could be resolved, and its anisotropy factor was shown to be correctly predicted, as demonstrated in Figure …”
Section: Spectroscopic Methods To Analyze Products Of Model Heterogenmentioning
confidence: 88%
“…In an exemplary fruitful work between theoreticians and experimentalists, together with Santoro, we revealed another benefit of CD‐REMPI‐MS studies on jet‐cooled molecules . Based on vibronically resolved spectra of 1‐phenylethanol, the anisotropy factors of the molecule were calculated, and it was found that the assignment of vibronic transitions could be done with higher confidence when experimental anisotropy factors are also taken into account .…”
Section: Spectroscopic Methods To Analyze Products Of Model Heterogenmentioning
confidence: 99%
See 3 more Smart Citations